2010
DOI: 10.1245/s10434-010-1027-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Perineural Invasion in Patients with Gastric Cancer Who Underwent Curative Resection

Abstract: Our results showed that the frequency of PNI was high in patients with gastric cancer who underwent curative gastrectomy and the proportion of PNI positivity increased with progression and clinical stage of disease. PNI may be useful in detecting patients who had poor prognosis after curative resection in gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
72
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 21 publications
10
72
1
Order By: Relevance
“…PNI positive found 31.7% in gastric cancer (Tianhang et al, 2008) and Bilici at al. indicated that PNI positive 75.6% in patients who resected curative intent (Bilici et al, 2010). Last two studies demonstrated PNI independent prognostic factor on survival (Tianhang et al, 2008;Bilici et al, 2010).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…PNI positive found 31.7% in gastric cancer (Tianhang et al, 2008) and Bilici at al. indicated that PNI positive 75.6% in patients who resected curative intent (Bilici et al, 2010). Last two studies demonstrated PNI independent prognostic factor on survival (Tianhang et al, 2008;Bilici et al, 2010).…”
Section: Resultsmentioning
confidence: 89%
“…Prior few studies demonstrated PNI positivity was from 31.7 to 75.6% (Duraker, 2003;Bilici et al, 2010). This situation may be each study had different patients population based of time diagnosis stage, clinicopathological features and demonstrated different technical stained PNI.…”
Section: Ta B L E 1 C a S S O C I A T I O N B E T W E E N P N I A Nmentioning
confidence: 96%
See 1 more Smart Citation
“…Perineural invasion, which is also called neurotropic carcinomatous spread or perineural spread, is the infiltration of neural fascicles or perineurium by tumor cells. Recent studies have proven that the presence of perineural invasion is an independent prognostic factor for survival and may contribute to the understanding of relapse or metastasis (16 Values were expressed as median (minimum-maximum) or n (%). Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…It was first reported in European literature during the mid-1800s by scientists who described head and neck cancer that exhibited a predilection for growth along nerves as they made their way toward the intracranial fossa (1). PNI has since emerged as a prognostic factor in numerous malignancies, including head and neck, pancreatic cancer, prostate and gastrointestinal cancer types (2)(3)(4)(5). PNI has been generally accepted as a poor prognostic factor in head and neck squamous cell carcinoma (HNSCC) (6).…”
Section: Introductionmentioning
confidence: 99%